2011
DOI: 10.1111/j.1600-0501.2010.02126.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat production during different ultrasonic and conventional osteotomy preparations for dental implants

Abstract: Ultrasonic implant site preparation is more time consuming and generates higher bone temperatures than conventional drilling. However, with the levels of irrigation, ultrasonic implant site preparation can be an equally safe method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
104
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(125 citation statements)
references
References 24 publications
9
104
0
5
Order By: Relevance
“…A serra pneumática para corte de osso, além dos danos térmicos, também criou múltiplas microfissuras na superfície óssea cortada; esses danos foram associados à fricção mecânica da serra, provocando um retardo no processo de reparo ósseo. Outro estudo 19 mostrou que o preparo cirúrgico para implantes utilizando ultrassom consumiu mais tempo e alcançou temperaturas mais altas ao osso do que a cirurgia convencional. Além disso, foi observado que o aumento de carga não teve nenhum efeito sobre o aumento da temperatura.…”
Section: Resultsunclassified
“…A serra pneumática para corte de osso, além dos danos térmicos, também criou múltiplas microfissuras na superfície óssea cortada; esses danos foram associados à fricção mecânica da serra, provocando um retardo no processo de reparo ósseo. Outro estudo 19 mostrou que o preparo cirúrgico para implantes utilizando ultrassom consumiu mais tempo e alcançou temperaturas mais altas ao osso do que a cirurgia convencional. Além disso, foi observado que o aumento de carga não teve nenhum efeito sobre o aumento da temperatura.…”
Section: Resultsunclassified
“…Speed, pressure, irrigation and bur shape have been identified as some of the most important factors influencing temperatures rising (3). The impact of pressure and irrigation has been also investigated with respect to implant site preparation with piezoelectric instruments (26,27).…”
Section: Resultsmentioning
confidence: 99%
“…Although the irrigation was not a specific issue of this investigation, it was proven to play an important role in reducing temperatures (22,27). However, the irrigation efficacy in limiting temperature elevation is evident in tests with warmed bone samples (37° C) (Fig.…”
Section: Irrigationmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study previously carried out on beagles, Bengazi et al 22 also found that osseointegration of implants is possible if the sites are prepared using conventional drill cutters with copious irrigation or by means of piezoelectric surgery. Results of previously conducted in vitro 29 and ex vivo 30 studies also evidenced that conventional osteotomy and osteotomy by means of piezoelectric surgery are equally safe methods for preparing sites for dental implants.…”
mentioning
confidence: 84%